How Supply Chain Finance Innovation Drives High-Quality Development in E-Commerce Logistics - Wang, Ying (Journal of Global Economy, Business and Finance, 2026)
Against the backdrop of emerging challenges confronting the high-quality development of domestic e-commerce logistics, investigating whether supply chain finance innovation can empower such development—particularly in support of constructing a unified national market—holds considerable practical significance. This paper empirically examines the impact of supply chain finance innovation on the high-quality development of e-commerce logistics using provincial panel data spanning the period 2013 to 2022. The empirical results yield three principal findings. First, supply chain finance innovation exerts a statistically significant positive effect on the high-quality development of e-commerce logistics. Second, this empowering effect exhibits notable regional and industrial structural heterogeneity. Specifically, the promotional impact diminishes progressively from the eastern to western regions in geographical space, and the effect is more pronounced under conditions of a more optimized industrial structure. Third, further decomposition of spatial effects reveals that the indirect effect of supply chain finance innovation on the high-quality development of e-commerce logistics is more substantial than its direct effect. These findings contribute to a deeper understanding of the mechanisms through which financial innovation within supply chains can facilitate logistics sector advancement, with important implications for regional development policy and industrial structure optimization.